دواعي وأسباب عدم الإفصاح عن المعلومات المتعلقة بأنشطة المسؤولية الاجتماعية في المصارف السودانية - Issa, Hassan Musa (Gezira Journal of Economic and Social Sciences, 2022)
هدفت الدراسة إلى الوقوف على دواعي وأسباب عدم إفصاح المصارف السودانية عن المعلومات المتعلقة بأنشطة المسؤولية الاجتماعية. أتبعت الدراسة المنهج الوصفي التحليلي، وتم جمع البيانات عن طريق استبيان تم توزيعه على الإدارات (أعضاء مجلس الإدارة ومديري الإدارة المالية) بالمصارف السودانية. توصلت الدراسة لنتائج عديدة أهمها أن عدم الإدراك التام لمفهوم محاسبة  المسؤولية الاجتماعية يعتبر أحد أسباب عدم تطبيقها، وأن القياس والإفصاح عن الأداء الاجتماعي للمصارف السودانية لا يحظى بالقدر الكافي من الاهتمام من جانب الجمعيات المحاسبية المهنية، بالإضافة إلى عدم توافر نماذج ملائمة للإفصاح عن المعلومات المتعلقة بالمسؤولية الاجتماعية. واختتمت الدراسة بعدة توصيات أهمها وضع نموذج أو نظام محاسبي واضح وسهل التطبيق ويأخذ في الاعتبار كلاً من التكاليف والمنافع الاجتماعية والإفصاح عنها في القوائم والتقارير المالية المنشورة، إضافة إلى إصدار معايير للمحاسبة عن المسؤولية الاجتماعية في إطار استكمال جهود التطوير المهني للمحاسبة في السودان.         Abstract The study aims to detect the Justifications and reasons that prevent the Sudanese banks to disclose information relating to social responsibility. The study adopted descriptive analytical methodology; to collect the data a questioner was designed and handed out to the mangers (Board of Directors and Financial Affairs Management). The study arrived at a number of results, the most important of which are: the incomplete realize of managers in Sudanese banks of the concept of social responsibility accounting, classified as one of reasons affecting its application: it was also clear that measurement and disclosure of the social performance in the Sudanese banks do not have adequate amount of concern from the part of the accounting professional societies: unavailability of appropriate models  to disclosure the information's relating to social responsibility accounting. The study concluded with a number of recommendations, the most important of which were: professional and scientific corporations in Sudan should adopt the issuance of social responsibility standards within the framework of completing the efforts of professional development of accounting in Sudan; The study recommends the necessity of setting a clear and easily applicable model or accounting system which taking in consideration both social costs and benefits and disclose about them in published  financial statements and reports.